The Experience of marketing researches in the study of Japanese at Japanese department (Journal of Oriental Studies, 2017)
This article assesses study the language at the Japanese department atuniversity level. First it looks at the main reasons for decline in a numberstudents who study the language at the Japanese department at universitylevel. Second, the article analyses various tools used by foreign universitiesto improve teaching skills in learning Japanese language. Third the articlesanalyses various marketing tools used to attract new students on the exampleand experience of foreign universities.